Parent and child psychopathological symptoms: the mediating role of parental emotion dysregulation. Issue 3 (20th May 2016) - Han, Zhuo Rachel; Lei, Xuemei; Qian, Jing; Li, Peipei; Wang, Hui; Zhang, Xutong
Abstract : Background: Parental psychopathological symptoms have been associated with a number of child psychological problems, yet little research has examined the role of parental emotion dysregulation on the intergenerational transmission of psychopathological symptoms. This study aims to examine the relationship between parents' and children's psychopathological symptoms with a focus on the mediating mechanism of parental emotion dysregulation on these relationships. Methods: Eighty‐nine Chinese parents and their school‐age children between the ages of 7 and 12 (49 males, M age   = 8.79, SD  = 1.81) participated in the study. In the initial phase of the study, parents filled out a series of questionnaires reporting their own psychopathological symptoms via SCL‐90 and difficulties with emotion regulation via Difficulties in Emotion Regulation Scale. After 9 months, the parents reported their children's internalizing and externalizing problems via Child Behavior Checklist, and the children self‐reported anxiety symptoms via Screen for Child Anxiety Related Emotional Disorders in the second phase of the study. Results: The results showed that parental emotion dysregulation played an important role as a mediator of the relationship between parental psychopathological symptoms and child internalizing problems and separation anxiety, which indicates that parents' mental health problems were significantly associated with their difficulties with emotion regulation, which in turn led to more internalizing problems and separation anxiety in their children. However, we did not find a mediating effect of parental emotion dysregulation on the links between parent psychopathology and child externalizing problems or other types of self‐reported anxiety symptoms. Conclusions: Our findings highlighted the importance of implementing more psycho‐education programs that specifically target parents' emotion regulation abilities in both community and clinical settings to ameliorate the intergenerational transmission of psychopathological symptoms between generations.